Incremental Validity of the Subscales of the Emotional Regulation Related to Testing Scale for Predicting Test Anxiety. (September 2015) - Feldt, Ronald; Lindley, Kyla; Louison, Rebecca; Roe, Allison; Timm, Megan; Utinkova, Nikola
The Emotional Regulation Related to Testing Scale (ERT Scale) assesses strategies students use to regulate emotion related to academic testing. It has four dimensions: Cognitive Appraising Processes (CAP), Emotion-Focusing Processes (EFP), Task-Focusing Processes (TFP), and Regaining Task-Focusing Processes (RTFP). The study examined the factor structure of each dimension and the incremental validity of the ERT subscales ( N = 213 undergraduates). Confirmatory factor analysis indicated good fit for CAP and EFP dimensions. TFP and RTFP models had poor fit. The TFP dimension appears to involve a two-factor structure, which may account for why it has been observed to have low internal consistency reliability across studies. Subscales of CAP and EFP dimensions resulted in statistically significant increments in R 2 after accounting for self-efficacy for learning and metacognitive self-regulation of learning. The TFP dimension and RTFP subscales did not exhibit incremental validity. The importance of assessing self-regulation of emotion and learning is emphasized.